PENGARUH PENGGUNAAN SOSIAL MEDIA WHATSAPP TERHADAP PENINGKATAN PENJUALAN OBAT BEBAS, OBAT BEBAS TERBATAS, OBAT RESEP, VITAMIN DAN ALAT KESEHATAN DI APOTEK WONOMULYO - Miftahur Rahman Hafid (Lembaga Pengembangan Kinerja Dosen, 2025)
The swift advancement of information technology has a significant influence on corporate operations of all sizes that employ advanced technology in conducting their commercial purposes. Advancements in the digital realm necessitate that company professionals, particularly those in the pharmaceutical industry, enhance their digital marketing and communication strategies with clients. A pharmacy is a retail establishment where pharmacists engage in the practice of pharmacological medicine. In addition to providing pharmaceutical services, pharmacies are classified as a commercial sector under the Indonesian Standard Industrial Classification (KBLI) with code 47721, which specifically refers to the retail trade of pharmaceutical products and pharmaceuticals for human use in pharmacies. The objective of this study is to assess the impact of utilising the Whatsapp social media platform on the augmentation of sales for over-the-counter pharmaceuticals, prescription drugs, vitamins, and medical gadgets at Wonomulyo Pharmacy. The selected research approach is descriptive analysis using the purposive sampling methodology. The data collecting methods include interviews, formal documentation, and participant observation. The study's findings revealed a remarkable 91.31% surge in sales achieved through WhatsApp media compared to the intended goal. The study concludes that the promotion plan using WhatsApp social media offers advantages such as market expansion, elevated sales turnover, attraction of new customers, and serves as a promotional medium